2018
DOI: 10.1111/aor.13343
|View full text |Cite
|
Sign up to set email alerts
|

Technical Indicators to Evaluate the Degree of Large Clot Formation Inside the Membrane Fiber Bundle of an Oxygenator in an In Vitro Setup

Abstract: The most common technical complication during ECMO is clot formation. A large clot inside a membrane oxygenator reduces effective membrane surface area and therefore gas transfer capabilities, and restricts blood flow through the device, resulting in an increased membrane oxygenator pressure drop (dpMO). The reasons for thrombotic events are manifold and highly patient specific. Thrombus formation inside the oxygenator during ECMO is usually unpredictable and remains an unsolved problem. Clot sizes and positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…The relationship between oxygenator resistance and clot volume thus seems to become more quantitative at higher values, hence the stronger correlation with the quantitative OXBV value. This is in line with a study by Kaesler et al who showed that the increase in oxygenator pressure drop is modest up to a clot volume of 65 mL, and reports that pressure drop remains a vague indicator and seems to be reliable only in already advanced clotting stages [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relationship between oxygenator resistance and clot volume thus seems to become more quantitative at higher values, hence the stronger correlation with the quantitative OXBV value. This is in line with a study by Kaesler et al who showed that the increase in oxygenator pressure drop is modest up to a clot volume of 65 mL, and reports that pressure drop remains a vague indicator and seems to be reliable only in already advanced clotting stages [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…Clots in low flow areas of an oxygenator will cause less resistance than clots in high flow areas [ 8 ]. Consequently, relative changes in oxygenator resistance are not proportional to the amount of clot formation [ 8 , 9 ]. Oxygen transfer performance can also be decreased by fluid accumulation in the gas compartment [ 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies from other institutions, injection of a thrombus-inducing substance from the inlet side chamber was strongly associated with a decrease in the gas exchange capability of the oxygenator. 13 According to previous findings and those of the present study, the thrombus formed in the inlet side chamber may affect the gas exchange capability of the oxygenator, although it is unlikely to be a source of thromboembolism. In this study, a thrombus was formed so as to adhere to the blood contact surface of the outlet-side housing.…”
Section: Discussionsupporting
confidence: 77%
“…However, there is still no reliable, easy to use method, which allows the prediction of thrombus formation at an early stage to adapt the anticoagulation strategy to the acute demand of the patient. 16 Special magnetic resonance imaging (MRI) methods make it possible to visualize thrombus formation in the system, but they require completely nonferromagnetic circuit components and imply a high level of technical and medical complexity. 17 , 18 …”
Section: Activation Of Coagulation and Anticoagulation Strategiesmentioning
confidence: 99%